Histochemical Differential Diagnosis and Polarization Optical Analysis of Amyloid and Amyloidosis - M. Bély (The Scientific World Journal)
Amyloidosis is characterized by extracellular deposition of protein fibrils of chemically heterogeneous composition. Early recognition and identification of amyloid deposits allows an early start of therapy, which may entail a better prognosis. Congo red staining according to Romhányi (1971) is a highly specific and sensitive method for early microscopic recognition of amyloidosis. The main and most important types of amyloidosis may be distinguished by classic histochemical methods of performate pretreatment according to Romhányi (1979), or by KMnO4 oxidation according to Wright (1977) followed by Congo red staining and viewed under polarized light. Differences in the speed of breakdown (disintegration) of amyloid deposits according to Bély and Apáthy allow a more precise distinction of various types of amyloid.